SISTEM INFORMASI PENCATATAN PENGUKURAN DAN PERHITUNGAN POLA DASAR PAKAIAN WANITA (STUDI KASUS : BUTIK CHANIAGO JAMBI) : Application for Processing Data on Seam Orders;Customers;Php;Products;Seam Orders. - -, Lisdarti (JURNAL AKADEMIKA, 2020)
In managing good stitching order data at the Chaniago Jambi Boutique in recording data archiving activities are still classified as manual, especially in ordering ginger, employees are still recording in the agenda book. That is what underlies the study of Jambi Chaniago Boutique. So that errors often occur in daily, weekly, monthly reporting, at this time a more structured order orders data management system is needed in order to accelerate data management. From that the researchers designed the application of stitch order data management which was considered important to help the Chaniago Boutique Boutique ordering section. In conducting research, researchers use several research methodologies, including field research as the main source in obtaining input data such as product, customer and order data for the purposes of processing data in systems, libraries, and laboratories. This application was built with the support of PHP programming language that is connected to the MySQL database with the final results in the form of reports and product information, customers and orders. Furthermore, the application that has been built can further assist Chaniago Jambi Boutique in building the initial foundation of data collection orders for digital stitches. From the results of this study, it can be concluded that the application of logistical data processing in the Caniago Jambi Boutique Clothing Pattern Calculation Application was made with the aim of assisting the Jambi Chaniago Boutique in processing data related to seam orders.